Climate change impacts on Moroccan agriculture and the whole economy: An analysis of the impacts of the Plan Maroc Vert in Morocco - Ismail Ouraich; Wallace E. Tyner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The paper provides estimates of economic impacts of climate change, compares these with historical impacts of drought spells, and estimates the extent to which the current Moroccan agricultural development and investment strategy, the Plan Maroc Vert, helps in agricultural adaptation to climate change and uncertainty. We develop a regionalized Morocco Computable General Equilibrium model to analyse the linkages of climate-induced productivity losses (gains) at the level of administrative and economic regions in Morocco. Yield projections are obtained from the joint-study by the Moroccan Ministry of Agriculture and Fisheries and the World Bank, in collaboration with the National Institute for Agricultural Research, the Food and Agriculture Organization of the United Nations, and the Direction of National Meteorology. We model the climate change impacts as productivity (or yield) shocks in the agricultural sector, and which are region- and crop-specific. The yield projections are for 2050, and introduced with respect to a 2003 baseline. With no adaptation, GDP impacts range from -3.1 per cent (worst-case scenario) to +0.4 per cent (best case scenario). The decline in GDP under the worst-case scenario results from a general contraction in economic aggregates. Accounting for the adaptation measures in the Plan Maroc Vert, the GDP impacts from climate change are reduced and range from -0.3 per cent to +3 per cent. Nonetheless, the adaptation potential of the Plan Maroc Vert is based upon the assumption of achieving the identified productivity-enhancement targets, and which remains questionable.
Keywords: O13; Q10; Q54; 330; CGE models; agricultural policy; adaptation; climate change; SRES scenarios; uncertainty